Counter-Hegemonic Consciousness in Melawa Devi’s Selected Songs - Shrestha, Tara Lal; Shrestha, Bidhya (International Research Journal of MMC, 2024)
This paper explores counter-hegemonic consciousness in Melawa Devi’s selected songs. Firstly, it talks about Melawa Devi as a singer exhibiting how her four phases of life transform her from a hegemonic character to a counter-hegemonic actor. Then it explores how she negotiating with power bloc plays counter-hegemonic actions as ‘organic intellectual’ in Antonio Gramscian term, and encourages the subalterns to subtly share views against hegemonic power structure. Finally, this paper critically presents Melawa Devi’s selected songs that carry counter-hegemonic consciousness.